The Islamic Worldview as the Foundation of Islamic Educational Civilization in the Age of Globalization - Rasyidin Rasyidin; Radinal Mukhtar Harahap (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Islamic education faces a structural paradox in the era of globalization: many institutions pursue institutional adaptation without commensurate epistemological renewal, thereby modernizing administration but not philosophy, digitizing the classroom but not the knowledge framework, and expanding access but not intellectual goals. Consequently, Islamic educational institutions remain institutionally intact but are conceptually weakened amid pressures from accreditation, global rankings, and the knowledge economy. This conceptual study aims to formulate a paradigm for the reconstruction of Islamic education that addresses the pressures of modernization, globalization, and technological disruption without diluting its epistemological identity and civilizational mission. This research employs a qualitative-conceptual design with a structured narrative review approach of 81 sources selected via a PRISMA-adapted procedure, coded using NVivo 14, cross-checked for inter-coder consistency, and analyzed dialectically based on the principle of immanent critique. Tracy’s quality framework is fully adopted to ensure methodological rigor. The analysis demonstrates that Tajdīd, the Islamization of knowledge, and the Islamic worldview cannot be treated as additive components but rather as constructs operating at distinct yet interdependent levels: institutional-pedagogical, epistemological, and civilizational. This distinction between operational levels constitutes the primary conceptual contribution that sets this analysis apart from previous syntheses. The article also addresses three substantial internal critiques: dialectical, historiographical, and operational, which are rarely addressed in the supporting literature. The findings yield three empirically testable propositions and three practical priorities for Islamic educational institutions, enabling Islamic education to transition from being a consumer of global paradigms to a producer of intellectual alternatives for 21st-century ethical reconstruction